A systemic problem cannot be solved systemically - Maldonado, Carlos Eduardo (Cinta de Moebio. Revista de Epistemología de Ciencias Sociales, 2023)
This paper is a short essay that claims that a systemic problem cannot be rightly understood and even less solved on the same level, in the same framework or with the same tools that entail the very same problem. This is a radical variation of Einstein’s idea set out in the context of the Copenhaguen debate according to which a problem cannot be solved if we do not change the conditions in which the problem arose originally. More exactly, a systemic problem cannot be tackled and solved with tools, approaches and rods of the very same kind, level, nature of framework that define the problem. To truly tackle and solve any problem, the approach, tools, concepts, models, and the like need have a higher or heavier calibre so to speak than the problem. Otherwise, we do not solve a problem at all. At its best, we displace it. This essay argues that to solve any systemic problem a complexity endeavour is needed. Reasons for the insufficiency of systems science and about the rationale of complexity theory are provided.